Is the World's Economic Center of Gravity Already in Asia? - Grether, Jean-marie; Mathys, Nicole (Université de Lausanne, Faculté des HEC, DEEP, 2008)
This paper proposes a simple measure of the World's Economic Center of Gravity (WECG) based on national GDP figures and the geographical location of the world's most important cities. This measure makes it possible to characterize the location of economic activity around the globe. It turns out that, over the 1975-2004 period, the WECG has shifted towards Asia, and the location of economic activity has become more evenly spread. On average, the distance to the WECG, which is highly correlated with the remoteness indicator frequently used in the trade gravity literature, has decreased more in Asian cities (-12%) and increased more in European cities (+16%).
Keywords: Geographical location of economic activity; center of gravity; spatial imbalances